De Novo DNA Methylation Is Required to Restrict T Helper Lineage Plasticity - Thomas, Rajan M. (American Society for Biochemistry and Molecular Biology, 2012)
Naïve CD4+ T cells are highly plastic and can differentiate into discrete lineages with unique functions during an immune response. Once differentiated, helper T cells maintain a stable transcriptional memory of their initial lineage choice and resist redifferentiation. During embryogenesis, de novo DNA methylation operates on the hypomethylated genome of the blastocyst to achieve tissue-specific patterns of gene expression. Similarly, the ifnγ promoter is hypomethylated in naïve T cells, but Th2, Th17, and iTreg differentiation is accompanied by substantial de novo DNA methylation at this locus. To determine whether de novo DNA methylation is required to restrict T helper lineage plasticity, we used mice with T cell-specific deletion of the methyltransferase DNMT3a. Induction of lineage-specific cytokines occurred normally in the absence of DNMT3a, however, DNMT3a-deficient Th2, Th17, and iTreg completely failed to methylate the ifnγ promoter. This was accompanied by an increase in the transcriptionally permissive trimethyl H3K4 mark, and a reduction in inhibitory H3K27 methylation at the ifnγ locus. Failed de novo methylation resulted in failed silencing of the ifnγ gene, as DNMT3a-deficient Th2, Th17, and iTreg cells produced significant levels of IFNγ following restimulation in the presence of IL-12. Therefore, DNMT3a-mediated DNA methylation restricts T helper plasticity by establishing an epigenetically silent chromatin structure at regulatory regions of the ifnγ gene.